The Association of Non-Dipterocarps (Fagaceae) with Mycorrhizae in Elevated CO2 Condition in Tekam Forest Reserve, Pahang - Mustafa Bakray Nur Aqilah; Azmi Nuralisya Amirah; Jamar Nurul Hidayah; Kin Thi Bee; Mansor Patahayah; Mohti Azian; Zohari Ahmad Fitri; Mohd Said Mohd Nizam (E3S Web of Conferences)
The gradual rise in atmospheric carbon dioxide (CO2) levels has indirectly impacted the structure of belowground communities, including arbuscular mycorrhizal fungi (AMF) associated with Fagaceae saplings in Southeast Asia’s tropical rainforests. This study aims to determine the composition of AMF spore morphotypes under elevated CO2 and ambient conditions at Tekam Forest Reserve, Pahang. Seventeen soil samples were collected using a stratified sampling method from saplings of three Fagaceae species, namely, Castanopsis inermis, Lithocarpus lucidus, and Lithocarpus rassa, under both elevated CO2 and ambient conditions. AMF spores were extracted using the wet sieving and decanting technique and subsequently identified using specialized keys and online resources. The data were analyzed for composition and abundance of AMF community between the two conditions. The study identified 35 spore morphotypes across the different species and environmental conditions. AMF exhibited higher diversity and more complex community structures under ambient conditions, with a total of 29 species, compared to 25 species under elevated CO2 conditions. Glomus was the most prevalent under both conditions. These results suggest that elevated CO2 levels can significantly alter AMF community composition and reduce overall diversity, highlighting the impact of rising CO2 on belowground ecosystems. The findings provide valuable insights into how climate change may affect AMF communities in tropical forests like Tekam FR, with potential consequences for forest health, nutrient cycling, and plant growth. This emphasizes the need for further research to fully understand the dynamics and their broader ecological implications.